Strategies for optimizing compliance of paediatric patients for seasonal antibacterial vaccination with sublingually administered PMBL - Rosaschino, F.; Cattaneo, L. (Acta Biomedica Atenei Parmensis, 2004)
The objective of this pilot study was to evaluate efficacy, tolerance and compliance of paediatric patients vis-à-vis a cycle of PMBL treatment (a sublingual tablet taken for ten consecutive days over three consecutive months). The study enrolled 89 children (65 randomised to the treated group and 24 to the control group). The study protocol included an enrolment check-up (T0) and follow-ups at two months (T1), three months (T2) and nine months (T3) following the end of treatment, during which episodes of RRI were recorded; the main blood chemistry, immunology and phlogosis parameters were measured, together with hepatic, renal and bone marrow toxicity indexes. The administration of PMBL led to a significant decrease in RRI in the treated group, not only among the same children in relation to the previous winter, but also in comparison with untreated children during the same winter (mean number of infective episodes per patient 7.84 vs. 4.78, p<0.05, in the first case; 6.78 vs. 4.78, p<0.05, in the second case). White blood cell count showed a drop in the treated group as opposed to an increase in the untreated group, but there were no statistically significant differences in the intergroup analysis or in the intragroup one. Phlogosis indexes (PCR and plasma mucoprotein) in the treated group fell following treatment with PMBL, and this is statistically significant not only in the intragroup analysis but also the intergroup one. Mean values of B-lymphocytes in the treated group seemed to increase significantly following treatment, which was not the case in the untreated group. The variations in all the blood chemistry indexes for toxicity were far from significant and they remained within the norm, without significant clinical manifestations of side-effects of drug intolerance. As to evaluation of patient compliance, use of the device we describe enabled acceptable compliance with treatment even in the youngest children, similar to the compliance observed among appropriately motivated older children.